HANPP calculated from land cover as indicator of ecological sustainability - Josep A. Garí (European Society for Ecological Economics and Université de Versailles; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This is the inaugural paper that introduced a new indicator of sustainability, which the author coins HANPP: Human Appropriation of Net Primary Production. This indicator estimates the extent of human use of ecological and land resources, contributing to the nascent ecological-footprint movement in the 1990s. The paper describes the concept of HANPP and provides a set of rudimentary algorithms and metrics for measuring it, mainly through data on land cover and land use. It also provides a preliminary, comparative estimation of HANPP in two socially and ecologically dissimilar countries – Ecuador and the Netherlands – and offers a brief discussion on the potential role of HANPP in assessing sustainability issues, from biodiversity conservation to land use management. In effect, after this paper, HANPP started to be used and further developed in the field of ecological economics, becoming a practical tool to assess and guide land-use policy and management. This paper illustrates the humble beginnings of an indicator that has contributed to building the robust network of metrics now available to assess and advance socio-economic pathways to sustainable development.
Conference: Proceedings of the International Conference: Ecology, Society, Economy. European Society for Ecological Economics and Université de Versailles, Paris, tome I: section V-E.; Additional information: This is the seminal paper that introduced and named a new indicator of sustainability: HANPP (Human Appropriation of Net Primary Production).
Keywords: Q00; Q01; R14; 330; HANPP; Land use; Ecological economics; Sustainability indicators; Ecological footprint